At Westonci.ca, we make it easy for you to get the answers you need from a community of knowledgeable individuals. Get expert answers to your questions quickly and accurately from our dedicated community of professionals. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
To determine which equations represent circles with the smallest and largest radii, we first need to rewrite each equation in the standard form of a circle's equation: [tex]\((x-h)^2 + (y-k)^2 = r^2\)[/tex]. This is accomplished by completing the square.
Let's complete the square for each equation:
### Equation 1:
[tex]\[ 2x^2 + 2y^2 + 16x - 4y + 30 = 0 \][/tex]
1. Divide by 2 to simplify:
[tex]\[ x^2 + y^2 + 8x - 2y + 15 = 0 \][/tex]
2. Move the constant term to the right side:
[tex]\[ x^2 + y^2 + 8x - 2y = -15 \][/tex]
3. Complete the square for [tex]\(x\)[/tex] and [tex]\(y\)[/tex]:
[tex]\[ x^2 + 8x + 16 + y^2 - 2y + 1 = -15 + 16 + 1 \][/tex]
4. Factor the perfect squares and solve for the right side:
[tex]\[ (x + 4)^2 + (y - 1)^2 = 2 \][/tex]
Here, the radius [tex]\(r_1 = \sqrt{2}\)[/tex].
### Equation 2:
[tex]\[ x^2 + y^2 + 6x - 4y - 20 = 0 \][/tex]
1. Move the constant term to the right side:
[tex]\[ x^2 + y^2 + 6x - 4y = 20 \][/tex]
2. Complete the square for [tex]\(x\)[/tex] and [tex]\(y\)[/tex]:
[tex]\[ x^2 + 6x + 9 + y^2 - 4y + 4 = 20 + 9 + 4 \][/tex]
3. Factor the perfect squares and solve for the right side:
[tex]\[ (x + 3)^2 + (y - 2)^2 = 33 \][/tex]
Here, the radius [tex]\(r_2 = \sqrt{33}\)[/tex].
### Equation 3:
[tex]\[ 4x^2 + 4y^2 - 16x - 24y + 51 = 0 \][/tex]
1. Divide by 4 to simplify:
[tex]\[ x^2 + y^2 - 4x - 6y + \frac{51}{4} = 0 \][/tex]
2. Move the constant term to the right side:
[tex]\[ x^2 + y^2 - 4x - 6y = -\frac{51}{4} \][/tex]
3. Complete the square for [tex]\(x\)[/tex] and [tex]\(y\)[/tex]:
[tex]\[ x^2 - 4x + 4 + y^2 - 6y + 9 = -\frac{51}{4} + 4 + 9 \][/tex]
4. Calculate the right side:
[tex]\[ -\frac{51}{4} + 4 + 9 = -\frac{51}{4} + \frac{16}{4} + \frac{36}{4} = -\frac{51 - 16 - 36}{4} = \frac{1}{4} \][/tex]
5. Factor the perfect squares:
[tex]\[ (x - 2)^2 + (y - 3)^2 = \frac{1}{4} \][/tex]
Here, the radius [tex]\(r_3 = \sqrt{\frac{1}{4}} = \frac{1}{2}\)[/tex].
### Summary:
1. Radius for Equation 1: [tex]\( r_1 = \sqrt{2} \)[/tex]
2. Radius for Equation 2: [tex]\( r_2 = \sqrt{33} \)[/tex]
3. Radius for Equation 3: [tex]\( r_3 = \frac{1}{2} \)[/tex]
Smallest radius: [tex]\( \frac{1}{2} \)[/tex] (Equation 3: [tex]\( 4x^2 + 4y^2 - 16x - 24y + 51 = 0 \)[/tex])
Largest radius: [tex]\( \sqrt{33} \)[/tex] (Equation 2: [tex]\( x^2 + y^2 + 6x - 4y - 20 = 0 \)[/tex])
The table should be completed as follows:
| Radius | Equation |
|---------------|------------------------------------------------|
| Smallest | [tex]\( 4 x^2 + 4 y^2 - 16 x - 24 y + 51 = 0 \)[/tex] |
| Largest | [tex]\( x^2 + y^2 + 6 x - 4 y - 20 = 0 \)[/tex] |
Let's complete the square for each equation:
### Equation 1:
[tex]\[ 2x^2 + 2y^2 + 16x - 4y + 30 = 0 \][/tex]
1. Divide by 2 to simplify:
[tex]\[ x^2 + y^2 + 8x - 2y + 15 = 0 \][/tex]
2. Move the constant term to the right side:
[tex]\[ x^2 + y^2 + 8x - 2y = -15 \][/tex]
3. Complete the square for [tex]\(x\)[/tex] and [tex]\(y\)[/tex]:
[tex]\[ x^2 + 8x + 16 + y^2 - 2y + 1 = -15 + 16 + 1 \][/tex]
4. Factor the perfect squares and solve for the right side:
[tex]\[ (x + 4)^2 + (y - 1)^2 = 2 \][/tex]
Here, the radius [tex]\(r_1 = \sqrt{2}\)[/tex].
### Equation 2:
[tex]\[ x^2 + y^2 + 6x - 4y - 20 = 0 \][/tex]
1. Move the constant term to the right side:
[tex]\[ x^2 + y^2 + 6x - 4y = 20 \][/tex]
2. Complete the square for [tex]\(x\)[/tex] and [tex]\(y\)[/tex]:
[tex]\[ x^2 + 6x + 9 + y^2 - 4y + 4 = 20 + 9 + 4 \][/tex]
3. Factor the perfect squares and solve for the right side:
[tex]\[ (x + 3)^2 + (y - 2)^2 = 33 \][/tex]
Here, the radius [tex]\(r_2 = \sqrt{33}\)[/tex].
### Equation 3:
[tex]\[ 4x^2 + 4y^2 - 16x - 24y + 51 = 0 \][/tex]
1. Divide by 4 to simplify:
[tex]\[ x^2 + y^2 - 4x - 6y + \frac{51}{4} = 0 \][/tex]
2. Move the constant term to the right side:
[tex]\[ x^2 + y^2 - 4x - 6y = -\frac{51}{4} \][/tex]
3. Complete the square for [tex]\(x\)[/tex] and [tex]\(y\)[/tex]:
[tex]\[ x^2 - 4x + 4 + y^2 - 6y + 9 = -\frac{51}{4} + 4 + 9 \][/tex]
4. Calculate the right side:
[tex]\[ -\frac{51}{4} + 4 + 9 = -\frac{51}{4} + \frac{16}{4} + \frac{36}{4} = -\frac{51 - 16 - 36}{4} = \frac{1}{4} \][/tex]
5. Factor the perfect squares:
[tex]\[ (x - 2)^2 + (y - 3)^2 = \frac{1}{4} \][/tex]
Here, the radius [tex]\(r_3 = \sqrt{\frac{1}{4}} = \frac{1}{2}\)[/tex].
### Summary:
1. Radius for Equation 1: [tex]\( r_1 = \sqrt{2} \)[/tex]
2. Radius for Equation 2: [tex]\( r_2 = \sqrt{33} \)[/tex]
3. Radius for Equation 3: [tex]\( r_3 = \frac{1}{2} \)[/tex]
Smallest radius: [tex]\( \frac{1}{2} \)[/tex] (Equation 3: [tex]\( 4x^2 + 4y^2 - 16x - 24y + 51 = 0 \)[/tex])
Largest radius: [tex]\( \sqrt{33} \)[/tex] (Equation 2: [tex]\( x^2 + y^2 + 6x - 4y - 20 = 0 \)[/tex])
The table should be completed as follows:
| Radius | Equation |
|---------------|------------------------------------------------|
| Smallest | [tex]\( 4 x^2 + 4 y^2 - 16 x - 24 y + 51 = 0 \)[/tex] |
| Largest | [tex]\( x^2 + y^2 + 6 x - 4 y - 20 = 0 \)[/tex] |
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for visiting. Our goal is to provide the most accurate answers for all your informational needs. Come back soon. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.